Medical Image Encryption Using Modified Identity Based Encryption - Purnamasari, Dian Neipa; Sudarsono, Amang; Kristalina, Prima (EMITTER International Journal of Engineering Technology, 2019)
The development of technology and communication also affects the level of security needed for digital image transmission. It is known that digital images now have important meanings in both communication and video conference. In this paper, we propose a security method for medical encryption in the form of images. The proposed method is implemented in the modified Identity-Based Encryption scheme. The encryption algorithm used is Elliptic Curve Cryptography (ECC) to generate key pairs and the Advanced Encryption Standard (AES) to generate symmetric keys and encrypt process. This method has been tested based on computation time, histogram analysis and statistical analysis. The results of the test were obtained that the proposed method was resistant to multiple attacks despite having slower computing time. The proposed compute time error percentage is 1.69% for key generator stages and 0.07% for total compute time at the encrypt-decrypt stage.